EFFECTIVENESS OF PHARMACOLOGY IN THE TREATMENT OF POSTPARTUM DISEASES - S. M. Djumanov; B. R. Kokilov (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides literature information on etiopathogenesis, treatment and prevention of postpartum hemiparalysis.